Pravo pristupa podacima u službenoj evidenciji / The Right to Access Official Records Data - Ajanović, Enver (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The BiH Parliamentary Assembly adopted the Law on Freedom of Access to Information in BiH in 2000 and amended it in 2006, 2009, 2011 and 2013. In the Law’s preamble, only Article IV paragraph 4 under item a) of the Constitution of BiH is determined as a formal legal basis. The preamble does not contain a substantive legal basis, as there is no clear explicit legal basis for this law in the BiH Constitution. An indirect legal basis is contained in the European Convention for the Protection of Human Rights and Fundamental Freedoms in the provision on freedom of expression, as this freedom includes the freedom to receive and impart information. Only the EU Charter of Fundamental Rights contains the true legal basis for this law. In accordance with the administrative work of performing other administrative and professional tasks and the purpose of this general legal act, it is necessary to change its name to the Law on the Right of Access to Data in Official Records.